Pancreatic stellate cells in pancreatic cancer: as potential targets for future therapy - Wang, Zhengfeng; He, Ru; Dong, Shi; Zhou, Wence (Frontiers in Oncology, 2023)
Pancreatic cancer is a malignant tumour of the gastrointestinal tract with a high degree of malignancy, late detection, high mortality, poor patient prognosis and a lack of effective treatment options. Therefore, there is an urgent need to explore new treatment options for pancreatic cancer. Pancreatic stellate cells are one of the constituent cells of the mesenchymal cell layer of the pancreatic tumour microenvironment and play an important role in regulating the pancreatic tumour microenvironment by interacting with pancreatic cancer cells. In this review, the anti-tumour immune response inhibited by pancreatic stellate cells, the mechanisms that promote pancreatic cancer progression and some preclinical studies targeting pancreatic cancer progression are presented, with a view to providing some theoretical references for the treatment of pancreatic cancer.